Creep Strain and Stress Analysis in Laminated Composite Pres-sure Vessels - Ahmad Reza Ghasemi; Komeil Hosseinpour (Mechanics of Advanced Composite Structures)
This study investigates the time-dependent long-term creep strain in a composite cylinder made of glass/vinylester with a unidirectional ply. The cylinder is subjected to an internal pressure and the boundary condition is free–free and acts as thermal insulation. The classical lamination theory (CLT) is used to derive the governing equations as a second-order equation to determine the radial, circum-ferential, axial, and effective stresses in the cylinder wall. The distribution of the radial and circumferential creep strains is based on the Schapery’s single integral model for nonlinear viscoelastic materials. This study focuses on the effect of the orientation of the fibers on the creep strain distribution in the wall of a cylinder. The results show that the creep strain is lower when  than at . As the angle of the fibers increases, the distribution of the creep strain becomes more uniform.